ESSAYS IN OPTIMAL MONETARY POLICY AND STATE-SPACE ECONOMETRICS - Scott, C. Patrick (Kansas State University, 2013)
This dissertation consists of three essays relating to asymmetric preferences in optimal monetary policy models. Optimal monetary policy models are theoretical optimal control problems that seek to identify how the monetary authority makes decisions and ultimately formulate decision rules for monetary policy actions. These models are important to policy makers because they help to define expectations of policy responses by the central bank. By identifying how researchers perceive the central bank’s actions over time, the monetary authority can identify how to manage those expectations better and formulate effective policy measures. In chapter 1, using a model of an optimizing monetary authority which has preferences that weigh inflation and unemployment, Ruge-Murcia (2003a; 2004) finds empirical evidence that the monetary authority has asymmetric preferences for unemployment. We extend this model to weigh inflation and output and show that the empirical evidence using these series also supports an asymmetric preference hypothesis, only in our case, preferences are asymmetricforoutput. Wealsofindevidencethatthemonetaryauthoritytargetspotential output rather than some higher output level as would be the case in an extended Barro and Gordon (1983) model. Chapter 2 extends the asymmetric monetary policy problem of Surico (2007) by relaxing the assumption that inflation and interest rate targets are constant using a time varying parameter approach. By estimating a system of equations using iterative maximum likeli- hood, all of the monetary planner’s structural parameters are identified. Evidence indicates that the inflation and interest rate targets are not constant over time for all models esti- mated. Results also indicate that the Federal Reserve does exhibit asymmetric preferences toward inflationary and output gap movements for the full data sample. The results are robust when accounting for changing monetary policy targeting behavior in an extended model. The asymmetry for both inflation and output gaps disappears over the post-Volcker subsample, as in Surico (2007). In chapter 3, Walsh (2003b)’s speed limit objective function is generalized to allow for asymmetry of policy response. A structural model is estimated using unobserved compo- nents to account for core inflation and measure the output gap as in Harvey, Trimbur and Van Dijk (2007) and Harvey (2011). Full sample estimates provide evidence for asymmetry in changes in inflation over time, but reject asymmetry for the traditional speed limit for the output gap. Post-Volcker subsample estimates see asymmetry disappear as in a more traditional asymmetric preferences model like Surico (2007).
Keywords: Monetary policy, Econometrics, Kalman filter; Economics (0501)